2016
DOI: 10.1111/jan.12995
|View full text |Cite
|
Sign up to set email alerts
|

Mental health nurses' experiences of managing work‐related emotions through supervision

Abstract: The analytical construct of feeling rules allows us to connect individual emotional experiences to shared normative discourses, highlighting how these shape emotional processes taking place in supervision. This understanding supports an explanation of how supervision may positively influence nurses' emotion management and perhaps reduce burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…However, there is a sense that this traditional hierarchy is still in place. MacLaren et al () reported that, although mental health nurses regard themselves as skilled and experienced, they continue to experience an in‐built inferiority to professions such as medicine and psychology. It is crucial that mental health nurses continue to develop as a profession and that they instil recovery‐orientated values into the organizations in which they work so that such an ethos can influence all members of the inter/transdisciplinary team (Cusack et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a sense that this traditional hierarchy is still in place. MacLaren et al () reported that, although mental health nurses regard themselves as skilled and experienced, they continue to experience an in‐built inferiority to professions such as medicine and psychology. It is crucial that mental health nurses continue to develop as a profession and that they instil recovery‐orientated values into the organizations in which they work so that such an ethos can influence all members of the inter/transdisciplinary team (Cusack et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings from this small study suggest that, in keeping with other areas of nursing specialism, clinical supervision has the potential to improve staff wellbeing and patient care (Hyrkäs 2005;Snowden et al 2017;). Whilst most of the evidence for effectiveness of clinical supervision as a support mechanism for staff comes from mental health nursing (for example, Lakeman and Glasgow 2009;Maclaren et al 2016 ), its role is beginning to be appreciated in other settings, including community and hospice services (Abbott et al 2018;Chilvers and Ramsey 2009). Although the UK Government identified the need for and value of clinical supervision in 1993, it still may not be routinely available to all advanced practice / specialist nurses across the UK despite an increasingly demanding workload.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MacLaren et al . () suggested that benefits of supervision might be negated, because it takes great effort to address emotions in an institutional environment where emotions are generally suppressed. In line with this, the informants in the present study spoke of a preference to develop their skills in small and safe ‘unofficial’ forums, which could be seen as flexible alternatives to supervision without managerial involvement, and where they could understand themselves as taking agency.…”
Section: Discussionmentioning
confidence: 99%
“…; Duncan‐Grant ; MacLaren et al . ). In the present study, we explored the reasons for mental health hospital nursing staff members’ non‐participation in clinical supervision.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation